O mecônio contém potenciais biomarcadores associados a idade da matriz e a qualidade da pintainha poedeira - Olivieri, Otávio Cintra Lemos (2023)
Early identification of either good or poor-quality chicks is crucial for proper hatchery allocation and optimal farm flock composition. One approach to selecting chicks based on quality involves identifying biomarkers in biological samples. Concurrently, understanding the metabolic profile of chicks from different-aged breeders is essential for developing strategies to mitigate the age-related effects on hatchability. This study investigated whether chick quality and breeder age influence the metabolic profile in layer chick meconium. A total of 198 chicks from Lohmann breeder hens, categorized as young, middle-aged, and old, were visually assessed for quality, and meconium samples were collected for metabolomic analysis. Good quality chicks exhibited 16 metabolites that varied across breeder ages with an overall accuracy of 72.9%. Using metabolite profiles, the accuracy for predicting if a chick originated from a young hen was 92.31%, with high sensitivity (92.30%) and specificity (93.75%). Four metabolites were discerned in poor-quality chicks with an overall accuracy of 66.17%. The Partial Least Squares Discriminant Analysis (PLS-DA) showed enhanced metabolite separation in good-quality chicks, with six metabolites exhibiting high area under the curve (AUC) values in chicks from young hens, namely "Thyrotropin releasing hormone" (TRH), "Creatine" (CR), "Semilepidinoside B" (SB), "Gly Pro Lys" (GPL), "Pirimicarb" (PIR), and "1α-hydroxy-23-[3 (1-hydroxy-1-methylethyl)phenyl]-22,22,23,23-tetradehydro-24,25,26,27-tetranorvitamin D3 / 1α-hydroxy-23-[3-(1-hydroxy-1-methylethyl)phenyl]-22,22,23,23-tetradehydro-24,25,26,27 tetranorcholecalciferol" (DT3). Not taking into account maternal age, five metabolites varied between good and poor-quality chicks, but with a low accuracy of 63.38% for quality discrimination. Chicks from young, middle-aged, and old hens exhibited 12, 11, and 2 varying metabolites between good and poor qualities, with accuracies of 74.46%, 70.83%, and 51.6%, respectively. Certain metabolites emerged as potential biomarkers to distinguish between good and poor-quality layer chicks from young age groups. These include "Z12-oxo-10Z-octadecenoic acid" (OXO), "Dihydro Isorescinnamine" (DI), "PS(O-16:0/15:0)" (PS), "N-stearoyl tryptophan" (NST), "Creatine" (CR), and "7-methyl-1 [(2S,3R,4S,5S,6R)-3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]oxy-1,4a,5,6,7,7a hexahydrocyclopenta[c]pyran-4-carboxylic acid" (7M) for chicks from young hens, “N – nitrosoguvacine” (NN), “Asn Phe” (AP), “AFMK” (AF), “HC Blue No.2” (HC2), “Pentahomomethionine” (PTN), “Hydroxyprolyl-Valine” (HV) for middle-aged, and “1-(O-alpha-D-mannopyranosyl)-29-keto-(1,3R,31R)-dotriacontanetriol” (OAM) for old ages. . This study represents the first in the literature to present potential biomarkers distinguishing layer chicks by maternal age and chick quality.